2021
DOI: 10.3390/foods10061183
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Compounds Profile and Antioxidant Capacity of Pitahaya Fruit Peel from Two Red-Skinned Species (Hylocereus polyrhizus and Hylocereus undatus)

Abstract: Pitahaya peel is a good source of bioactive polyphenols. However, the bound phenolics and their antioxidant activity remain unclear. The bound phenolics of pitahaya peel from two red-skinned species with red pulp (RP) and white pulp (WP) were released with different methods (acid, base, and composite enzymes hydrolysis). The results revealed that base hydrolysis was the most efficient method for releasing the bound phenolics from RP (11.6 mg GAE/g DW) and WP (10.5 mg GAE/g DW), which was 13.04-fold and 8.18-fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 36 publications
(47 reference statements)
2
10
0
Order By: Relevance
“…A recent study by Tang et al [5] demonstrated a strong correlation between antioxidant capacity and total phenolic compounds in the Pitahaya fruit peel, highlighting the Molecules 2021, 26, 7502 2 of 9 contribution of each phenolic compound (including CGAs) to overall antioxidant capacity. Results have shown that CGA, one of the major phenolic compounds found, did not contribute significantly to the antioxidant activity as an individual compound.…”
Section: Introductionmentioning
confidence: 97%
“…A recent study by Tang et al [5] demonstrated a strong correlation between antioxidant capacity and total phenolic compounds in the Pitahaya fruit peel, highlighting the Molecules 2021, 26, 7502 2 of 9 contribution of each phenolic compound (including CGAs) to overall antioxidant capacity. Results have shown that CGA, one of the major phenolic compounds found, did not contribute significantly to the antioxidant activity as an individual compound.…”
Section: Introductionmentioning
confidence: 97%
“…Among the bioactive compounds of pitaya peel, phenolics and betacyanins have attracted great attention due to their predominant content (Lourith & Kanlayavattanakul, 2013;Qin et al, 2020). It is reported that different phenolic acids (gallic acid, protocatechuic acid, caffeic acid, coumaric acid, ferulic acid) and flavonoids (flavonols, anthocyanins, flavones, isoflavonoids) are identified in pitaya peel and these compounds exhibit high antioxidant activity (Tang et al, 2021). Pitaya peel betacyanins include betanin, isobetanin, phyllocatin, isophyllocactin and hylocerenin, the antioxidant activity of which has widely been documented (Belhadj Slimen et al, 2017;Suh et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, betacyanins have purple color which can be considered as a good source of natural colorants. Therefore, fresh pitaya peel has been used as a potential material for extraction of phytochemicals in different studies (Chen et al, 2021;Jiang et al, 2021;Leong et al, 2019;Tang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…fruits. Nurliyana et al [5] also reported that Hu and Hp varieties had TPC between 3.75 and 19.72 mg GAE/100 g. Pasko [52], reported that the TPC in all samples was higher in water than methanol extracts and red-fleshed pitaya had the highest TPC, followed by white and yellow fleshed pitaya. The results for TPC in the fruits were consistent with Perez-Loredo [53], and Garcia-Cruz [54], who observed higher concentration of these compounds in red-fleshed than in white ones.…”
Section: Total Phenolic Content and Antioxidant Capacitymentioning
confidence: 92%
“…The fruit is highly decorative, with a bright red skin adorned with green scales. The flesh is white, juicy and delicious [3,5]. Pitaya fruits are consumed fresh or processed into juice, jellies, marmalades, jams, wine and beverages [6][7][8].…”
Section: Introductionmentioning
confidence: 99%